Evaluasi Pembelajaran Pendidikan Agama Islam Berbasis Kinerja dalam Pendidikan Pesantren - Sirajuddin Sirajuddin; Nia Wardani; Syarifah Rahmah (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study aims to describe and analyze the implementation of performance-based PAI learning evaluation in Islamic boarding school education and its contribution to strengthening students' morals and spirituality. This study applies a qualitative approach with a descriptive design. Data collection was conducted through field observations, in-depth interviews, and document reviews involving Islamic boarding school administrators, Islamic Religious Education (PAI) teachers, and students as research subjects. The results show that performance-based evaluation is implemented through the assessment of students' daily worship practices, attitudes, discipline, and manners. Evaluation functions as part of the ongoing development process, although it still requires strengthening in the aspects of assessment planning and documentation.